Evaluasi Usability Sistem Informasi Audit Internal Mutu pada Pusat Jaminan Mutu Universitas Brawijaya - Rian Rizki Prayogo; Ismiarta Aknuranda; Hanifah Muslimah Az-Zahra (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2018)
SIAIM is an application used by the Quality Assurance Center to improve their performance. For several months using SIAIM, users provide feedback on the use of SIAIM applications. User issues gleaned from feedback are about non-functioning "Clarification Input" features, disseminating the use of SIAIMs and the display of poor SIAIMs such as font colors and less attractive interface layouts. Therefore it is necessary to evaluate usability on SIAIM to explore deeper problems and measure the usability level of SIAIM. Usability evaluation is based on 5 aspects of usability efficiency, effectiveness, learnability, memorability and satisfaction. Data collection using usability testing method, interview and questionnaire. The result of the evaluation of usability that has been done shows that the usability level of SIAIM is good because the value of each aspect of usability is above the standard average. In addition, SIAIM applications still can be improved again because there are still some problems during the evaluation usability. Recommendations were given to improve the SIAIM based on the problems gained during the evaluation of usability.